Complex thinking and adopting artificial intelligence tools: a study of university students - Vázquez-Parra, José Carlos; Gonzalez-Gonzalez, Carina Soledad; Amézquita-Zamora, Juan Alberto; Cotino Arbelo, Andrea E.; Palomino-Gámez, Sergio; Cruz-Sandoval, Marco (Frontiers in Education, 2024)
In the next five years, artificial intelligence (AI) tools are expected to become commonplace in people's lives, especially in their work processes. Therefore, educational institutions feel intrinsically responsible for ensuring that their students acquire and develop competences associated with the appropriate use of this technology in their educational programs. However, what are the perceptions of students regarding the inclusion of artificial intelligence tools in their educational process and future careers, and what competencies can influence a greater adoption of this technology in the classroom? The objective of this article presents the results of an exploratory study in a sample population of students from a technological university in Mexico, in which their perception and openness towards the training and use of artificial intelligence tools for their professions was examined. Their perception of the development of complex thinking and its sub-competencies was evaluated, recognizing that complex thinking is a valuable cognitive skill to face changes in uncertain environments. The methodology of the study consisted of a multivariate descriptive statistical analysis using R software. The results determined a positive correlation between students' perceived improvement in the achievement of complex thinking competence and their perception of the use of AI tools. In conclusion, participants perceived the use of these tools as a feature of their profession, although they questioned whether this knowledge is included in their professional training. This article presents several findings that offer ample opportunities for future research.